Investigating the effect of job placement and promotion on work motivation and performance - Kurnadi, Kurnadi; Maharani, Anita; Hendrian, Hendrian (Privietlab, 2023)
The study sought to determine how job placement and promotion influenced employee performance, with work motivation serving as an intervening variable. The study is a descriptive, explanatory quantitative study. The population and sample size total 117 people. Data was acquired by questionnaire distribution and analysed using path analysis and the Sobel test. The study's findings indicate that job placement has a positive impact on employee motivation. Promotion has a favourable impact on employee motivation. The direct effect of work placement on employee performance was greater than the indirect effect of work placement through work motivation, showing that the direct effect is more powerful than the indirect effect. Because the direct effect of promotions on employee performance is greater than the indirect effect of promotions through work motivation, the direct effect takes precedence over the indirect effect. Work motivation, according to the study, entirely buffers the impact of job location and promotion on employee performance.